Compliant Joints with Remote Centre of Compliance for the Improvement of the Motion Accuracy of a Gantry Stage - Pöhlmann Patrick; Peukert Christoph; Merx Marcel; Müller Jens; Ihlenfeldt Steffen (Journal of Machine Engineering)
Gantry stages, which consist of two parallel acting servo drives, are commonly used in machine tools. One drawback of this concept is the crosstalk between both drives. This can lead to a limited bandwidth of the position control or to high reaction forces. One way to overcome these issues is the usage of joints to create an additional degree of freedom. One benefit of compliant joints is the variability to adjust the position of each joint’s centre of compliance to change the transfer matrix between the motion of the drives and the tool centre point. This paper addresses the placement of the joint’s centre of compliance in order to improve motion accuracy. The characteristics of the joints and their effect on the behaviour of the gantry stage are compared using analytic investigations as well as experimental results.